Offending Frequency and Responses to Illegal Monetary Incentives - Nguyen, Holly (Journal of quantitative criminology, 2022)
Objectives We examine how responsive offenders are to illegal monetary incentives. We draw from rational choice theory, prospect theory, and models of labor supply to develop expectations regarding the relationship between criminal efficiency, which is the average earnings per offense, and frequency of offending. Methods We use OLS, fixed effects, and first-difference estimators to analyze data from 152 incarcerated male inmates from Quebec, Canada to study within individual monthly changes in criminal efficiency and offending frequency. Results There is an inverse relationship between criminal efficiency and frequency of offending, net of individual fixed effects, for market crimes, but not property crimes. We also find that the supply of crime is inelastic, meaning it is not highly sensitive to illegal wage changes. Conclusions In the months that offenders have an average bigger pay-off per crime, they offended less frequently. We conjecture that this negative relationship could be explained by two mechanisms: an income effect and/or through reference dependence. However, we are not able to disentangle between the two mechanisms. Moreover, we note that criminal efficiency is likely endogenous and should be treated as such in future scholarship.